Direct somatic embryogenesis and plant regeneration in Garcinia indica Choiss - Thengane, Shubhada Ratnakar; Deodhar, Swapna R.; Bhosle, S. V.; Rawal, S. K. (Current Science, 2006)
Direct somatic embryogenesis without an intervening callus phase was induced from immature seeds of Gar- cinia indica Choiss. Woody plant medium supplemented with 6-benzyl amino purine (BAP) (4.44-22.19 mu m) alone or in combination with a-naphthaleneacetic acid (2.69 mu m) produces somatic embryos within a period of 2-3 weeks with 80% frequency. Embryo induction was observed all over the explant surface. Origin of the embryo was confirmed histologically from sub-epidermal layer of the seed. Maturation of these embryos was achieved after 12 weeks of culture on a medium containing BAP (16.08 mu m) in combination with indole-3-acetic acid (2.85-5.71 mu m) and/or kinetin (4.65 mu m). About 75% of the regenerated somatic embryos germinated into complete plantlets. The plantlets were acclimatized successfully with 92% survival in greenhouse.
Keywords: Garcinia indica; guttifereae; seeds; somatic embryos

Repetitive somatic embryogenesis and plant regeneration in Garcinia indica Choiss - Thengane, Shubhada Ratnakar; Deodhar, Swapna R.; Bhosle, S. V.; Rawal, S. K. (In Vitro Cellular & Developmental Biology-Plant, 2006)
Immature seeds of Garcinia indica Choiss. were excised from immature fruits and cultured on Lloyd and McCown (1980), woody plant medium (WPM) with different combinations of auxins and cytokinins. Somatic embryos were obtained on the media supplemented with 6-benzylaminopurine (BA; 2.2-22.1 mu M) alone or in combination with alpha-naphthalene acetic acid (NAA; 2.6 mu M) with 80% frequency within a period of 2-3 wk. Subculture of embryos on medium containing BA (16.0 mu M) supplemented with indole-3-acetic acid (IAA; 2.8-5.7 mu M) and/or kinetin (4.6 mu M) gave rise to clusters of secondary somatic embryos along with maturation of primary embryos. In subsequent subculture on hormone-free half-strength WPM, the embryo clusters germinated with an increase in the number of secondary somatic embryos. About 70% of somatic embryos germinated into complete plantlets, which were successfully established under greenhouse conditions.
Keywords: Garcinia indica; guttifereae; secondary somatic embryos; seeds; somatic embryos

Phylogenetic analysis, homology modelling, molecular dynamics and docking studies of caffeoyl-CoA-O- methyl transferase (CCoAOMT 1 and 2) isoforms isolated from subabul (Leucaena leucocephala) - Pagadala, Nataraj Sekhar; Arha, Manish; Reddy, P. S.; Kumar, Ranadheer; Sirisha, V. L.; Prashant, S.; Reddy, K. Janardhan; Khan, Bashir Mohammad; Rawal, S. K.; Kishor, P. B. Kavi (Journal of Molecular Modeling, 2009)
Caffeoyl coenzyme A O-methyltransferase (CCoAOMT) is an important enzyme that participates in lignin biosynthesis especially in the formation of cell wall ferulic esters of plants. It plays a pivotal role in the methylation of the 3-hydroxyl group of caffeoyl CoA. Two cDNA clones that code CCoAOMT were isolated earlier from subabul and in the present study; 3D models of CCoAOMT1 and CCoAOMT2 enzymes were built using the MODELLER7v7 software to find out the substrate binding sites. These two proteins differed only in two amino acids and may have little or no functional redundancy. Refined models of the proteins were obtained after energy minimization and molecular dynamics in a solvated water layer. The models were further assessed by PROCHECK, WHATCHECK, Verify_3D and ERRAT programs and the results indicated that these models are reliable for further active site and docking analysis. The refined models showed that the two proteins have 9 and 10 alpha-helices, 6 and 7 beta-sheets respectively. The models were used for docking the substrates CoA, SAM, SAH, caffeoyl CoA, feruloyl CoA, 5-hydroxy feruloyl CoA and sinapyl CoA which showed that CoA and caffeoyl CoA are binding with high affinity with the enzymes in the presence and absence of SAM. It appears therefore that caffeoyl CoA is the substrate for both the isoenzymes. The results also indicated that CoA and caffeoyl CoA are binding with higher affinity to CCoAOMT2 than CCoAOMT1. Therefore, CCoAOMT2 conformation is thought to be the active form that exists in subabul. Docking studies indicated that conserved active site residues Met58, Thr60, Val63, Glu82, Gly84, Ser90, Asp160, Asp162, Thr169, Asn191 and Arg203 in CCoAOMT1 and CCoAOMT2 enzymes create the positive charge to balance the negatively charged caffeoyl CoA and play an important role in maintaining a functional conformation and are directly involved in donor-substrate binding.
Keywords: Caffeoyl-CoA 3-O-methyl transferase; docking; Modelling; S-adenosyl homocysteine